Analisis Dampak Sosial dan Ekonomi Kebijakan Pengembangan Kawasan Mix Use di Kecamatan Jabon - Isna Fitria Agustina; Ricka Octaviani (Universitas Muhammadiyah Sidoarjo, 2016)
The purpose of this study is to describe the analysis of regional development policy mix use Jabon, from policy making, policy, to implementation and evaluation of policies. This study is also to expose social and economic impact of regional development policy mix use Jabon. Using qualitative research, with the informant as many as six people. The informants field staff of Settlement and Regional Infrastructure (Infrastructure) Planning Agency (Bappeda), Head of a Sub Jabon, staff Kupang Village, the Village Head Tambakkalisogo, Kedungpandan Village Head, and Head of DusunTelocor. The results of this study indicate that first, all policy was appropriate and good. Second, the formulation of policies have done well with the needs of the community. Third, in the implementation of regional development policy mix use Jabon from 2003 to 2016 was still limited to the construction of the road and not in accordance with the concept created. Evaluation until now has not been done by the government of Sidoarjo. Social impact is a positive impact in terms of education and health services increased. There are also negative impacts, road construction makes the location of prostitution in the area Telocor increasingly crowded. Economically there has been no impact is felt by the public.